Question about SoftMath Algebrator - Algebra Homework Solver (689076614429)

Hi,

a 6ya expert can help you resolve that issue over the phone in a minute or two.

best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

the service is completely free and covers almost anything you can think of (from cars to computers, handyman, and even drones).

click here to download the app (for users in the US for now) and get all the help you need.

goodluck!

Posted on Jan 02, 2017

If all sides are equal then 2x + 5 = 4x - 3

2x = 8

x = 4

so the perimeter is 3 times either expression above

3 * (8 + 5) = 39

.

2x = 8

x = 4

so the perimeter is 3 times either expression above

3 * (8 + 5) = 39

.

Jan 12, 2017 | The Computers & Internet

Assuming we're dealing with the straight line y=(-3/4)x+13. the y intercept is 13.

If we're really dealing with the hyperbola y=-3/4x+13 then there is no y intercept since there's a vertical asymptote at x=0.

If we're really dealing with the hyperbola y=-3/4x+13 then there is no y intercept since there's a vertical asymptote at x=0.

Mar 20, 2014 | Computers & Internet

3(4x-7) = 15
4x-7 = 45
4x = 52
x = 13

May 12, 2011 | Texas Instruments TI-83 Plus Calculator

One way is to use the Polynomial Root Finder and Simultaneous Equation Solver app.

Press the APPS key, then select PlySmlt2 and press ENTER. Press ENTER to get past the opening screen, then select "POLY ROOT FINDER" and press ENTER. Select the order of the polynomial and other settings as desired. Press F5 (the GRAPH key) to go to the next screen. Enter the polynomial coefficients, then press F5 to solve. The next screen will show you the roots (unless you selected real roots and the polynomial doesn't have any real roots).

If you don't have the app installed, you can download it from

http://education.ti.com/educationportal/sites/US/productDetail/us_poly_83_84.html

Press the APPS key, then select PlySmlt2 and press ENTER. Press ENTER to get past the opening screen, then select "POLY ROOT FINDER" and press ENTER. Select the order of the polynomial and other settings as desired. Press F5 (the GRAPH key) to go to the next screen. Enter the polynomial coefficients, then press F5 to solve. The next screen will show you the roots (unless you selected real roots and the polynomial doesn't have any real roots).

If you don't have the app installed, you can download it from

http://education.ti.com/educationportal/sites/US/productDetail/us_poly_83_84.html

Jan 20, 2011 | Texas Instruments TI-83 Plus Calculator

Type solve(exp1 and exp2 and exp3, {x,y,z})

See cap images

See cap images

Dec 15, 2010 | Texas Instruments TI-89 Calculator

4x+7=11 Solve for "x".

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

subtract 7 from each side of the equation

4x +7(-7)=11(-7) = 4x=4

divide both sides of the equation by 4

4x/4=4/4

therefore

x=1

Correct?

Dec 06, 2009 | 2006 Harley Davidson FXDI35 35th...

Hi,

This calculator does not have a Solve function or a solver. However this example of yours is very simple that you can do it by hand. If you do not mind I will show you how to solve it. Not everything needs a calculator.

You want to solve for x. OK

This calculator does not have a Solve function or a solver. However this example of yours is very simple that you can do it by hand. If you do not mind I will show you how to solve it. Not everything needs a calculator.

You want to solve for x. OK

- Start by gathering similar terms 4x-x =3x; -13+5 =-8
- Rewrite your equation as 3x+1=2x-8
- Make the +1 change side while changing its sign
- 4x+1 -1 = 2x-8 -1 or 4x=2x-9
- Make +2x on the Right hand side go to the left hand side, changing its sign in the process 4x-2x=-9 or 2x=-9
- Divide both members by 2. This gives
- x=-9/2 or -4.5 if a decimal result is required.

Dec 06, 2009 | Texas Instruments TI-30XA Calculator

Hello,

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is** added **to 4x. If I want the term in y alone on one side I perform the** inverse operation of addition**, a **substraction**. I subtract 4x from both sides.

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

**3y= - 4x+6**

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is**multiplied** by the number 3. To isolate y I have to perform the **inverse operation** of the multiplication, namely the division by 3

3y/3 =(-4x+6)/3. The left hand side is just y

**y= (-4x+6)/3.**

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

**y= -(4/3)*x +2.**

Hope it helps.

I am not lecturing you but I would rather you understand how to do the manipulations involved in isolating a variable.

You want to isolate y, Ok

Start stripping it of all that is not y.

3y + 4x =6. (Addition is commutative, I can change the order of addition)

The term with y is

3y+4x-4x=6-4x. But 4x-4x=0, and we are left with

This operation is sometimes summarized as make one term change side while changing its sign

It would do no harm to put the right side of the foregoing equation in parentheses. I do that to avoid errors)

3y= (-4x+6).

Now y is

3y/3 =(-4x+6)/3. The left hand side is just y

While result is correct, I can also open the parentheses

y= -4x/3 +6/3

Hope it helps.

Oct 22, 2009 | Texas Instruments TI-89 Calculator

6x+6=4x+12

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.

6x+6-4x=12

Since 6x and -4x are like terms, add -4x to 6x to get 2x.

2x+6=12

Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.

2x=-6+12

Add 12 to -6 to get 6.

2x=6

Divide each term in the equation by 2.

(2x)/(2)=(6)/(2)

Simplify the left-hand side of the equation by canceling the common factors.

x=(6)/(2)

Simplify the right-hand side of the equation by simplifying each term.

x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

Paul 3 years younger to his friend peter. In seven years, the product of their ages would be 5 more than the product of their ages 5 years ago. How old are they now?

Oct 31, 2008 | Texas Instruments TI-30XA Calculator

170 people viewed this question

Usually answered in minutes!

Learn my son.

×